Diagnosis of prion diseases by RT-QuIC results in improved surveillance. (25th August 2020) - Rhoads, Daniel D.; Wrona, Aleksandra; Foutz, Aaron; Blevins, Janis; Glisic, Kathleen; Person, Marissa; Maddox, Ryan A.; Belay, Ermias D.; Schonberger, Lawrence B.; Tatsuoka, Curtis; Cohen, Mark L.; Appleby, Brian S.
Abstract : Objective: To present the National Prion Disease Pathology Surveillance Center's (NPDPSC's) experience using CSF real-time quaking-induced conversion (RT-QuIC) as a diagnostic test, to examine factors associated with false-negative RT-QuIC results, and to investigate the impact of RT-QuICs on prion disease surveillance. Methods: Between May 2015 and April 2018, the NPDPSC received 10, 498 CSF specimens that were included in the study. Sensitivity and specificity analyses were performed on 567 autopsy-verified cases. Prion disease type, demographic characteristics, specimen color, and time variables were examined for association with RT-QuIC results. The effect of including positive RT-QuIC cases in prion disease surveillance was examined. Results: The diagnostic sensitivity and specificity of RT-QuIC across all prion diseases were 90.3% and 98.5%, respectively. Diagnostic sensitivity was lower for fatal familial insomnia, Gerstmann-Sträussler-Scheinker disease, sporadic fatal insomnia, variably protease sensitive prionopathy, and the VV1 and MM2 subtypes of sporadic Creutzfeldt-Jakob disease. Individuals with prion disease and negative RT-QuIC results were younger and had lower tau levels and nonelevated 14-3-3 levels compared to RT-QuIC–positive cases. Sensitivity was high throughout the disease course. Some cases that initially tested RT-QuIC negative had a subsequent specimen test positive. Including positive RT-QuIC cases in surveillance statistics increased laboratory-based case ascertainment of prion disease by 90% over autopsy alone. Conclusions: RT-QuIC has high sensitivity and specificity for diagnosing prion diseases. Sensitivity limitations are associated with prion disease type, age, and related CSF diagnostic results. RT-QuIC greatly improves laboratory-based prion disease ascertainment for surveillance purposes. Classification of evidence: This study provides Class III evidence that second-generation RT-QuIC identifies prion disease with a sensitivity of 90.3% and specificity of 98.5% among patients being screened for these diseases due to concerning symptoms.